(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
The article discusses the effective use of sensory integration therapy for children with motor development disorders. It describes the clinical manifestations, etiology and pathogenesis of dyspraxia in children. Attention is paid to both children with gross motor impairment (autism spectrum disorders, cerebral palsy) and children with predominantly fine motor and speech disorders. The relevance of the work is due to the fact that if there is a need to ensure sensory integration in the process of rehabilitation work with preschool children with motor development disorders, including not only children with special needs, the problem has not been studied fully. The category of such children is characterised by the presence of a pronounced dyspraxia syndrome in the absence of such diagnoses as ASD, cerebral palsy and muscle diseases. Nevertheless, they also suffer from motor and often cognitive delays and impaired perception of reality. Without special qualified assistance, this category of children is unable to comprehend the adapted curriculum of preschool and school education. The object of the study is the possibilities of early intervention for timely diagnosis and assistance to children with motor development disorders. The subject of the study is the method of sensory integration therapy as a method of correctional therapy for children with motor development disorders in the preschool period. The hypothesis of the study is that timely implementation of sensory integration therapy provides a positive result in the correctional program for children with motor development disorders (dyspraxia syndrome). The mechanisms of influence of sensory integration on the improvement of the child’s motor functions and the formation of the child’s ability to purposefully control the body in later life, further developing mental and sensory skills, are also considered in detail. The article draws attention to the importance of an individual approach in the therapy of children’s motor skills, taking into account the root cause of the disease, the need for in-depth modern diagnostics and the development of an integration plan with the development of compensation for tactile, vestibular and proprioceptive disorders. This article is aimed at the medical community and those interested in deepening their understanding of sensory integration methods, especially for the correction of motor skills in children.